Urine-derived stem cells: a sustainable resource for advancing personalized medicine and dental regeneration - Atia, Gamal A.; Abdal Dayem, Ahmed; Taher, Ehab S.; Alghonemy, Wafaa Y.; Cho, Ssang-Goo; Aldarmahi, Ahmed A.; Haque, Md Azizul; Alshambky, Abeer; Taymour, Noha; Ibrahim, Ateya M.; Zaghamir, Donia E.; Elmorsy, Ekramy M.; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Urine-based therapy, an ancient practice, has been utilized across numerous civilizations to address a wide range of ailments. Urine was considered a priceless resource in numerous traditional therapeutic applications due to its reported medicinal capabilities. While the utilization of urine treatment is contentious and lacks significant support from modern healthcare, the discovery of urine-derived stem cells (UDSCs) has introduced a promising avenue for cell-based therapy. UDSCs offer a noninvasive and easily repeatable collection method, making them a practical and viable option for therapeutic applications. Research has shown that UDSCs contribute to organ preservation by promoting revascularization and decreasing inflammatory reactions in many diseases and conditions. This review will outline the contemporary status of UDSCs research and explore their potential applications in both fundamental science and medical practice.